Isolation and characterization of a minor fimbria from Porphyromonas gingivalis. - Hamada, N (1996)
We have discovered two distinctly different fimbriae expressed by the same Porphyromonas gingivalis strain. The construction of a fimA mutant of P. gingivalis ATCC 33277 has previously been reported by N. Hamada et al. (Infect. Immun. 62:1696-1704, 1994). Expression of fimbriae on the surface of the fimA mutant and the wild-type strain, ATCC 33277, were investigated by electron microscopy. The wild-type strain produced long fimbrial structures extending from the cell surface, whereas those structures were not observed on the fimA mutant. However, short fimbrial structures were seen on the surface of the fimA mutant. The short fimbrial protein was purified from the fimA mutant by selective protein precipitation and chromatography on DEAE Sepharose CL-6B. We have found that the second fimbrial structure of P. gingivalis ATCC 33277 is distinct from the 41-kDa (43-kDa) major fimbrial protein (FimA). We provisionally call this protein minor fimbriae. The molecular mass of the minor fimbriae is 67 kDa as estimated by sodium dodecyl sulfate-polyacrylamide gel electrophoresis under reducing conditions after boiling at 100 degrees C. The component shows a ladder-like pattern at 80 degrees C under nonreducing conditions, suggesting a tendency to aggregate or polymerize. In immunoblotting analysis, anti-minor fimbria serum reacted with both the 100 degrees C- and the 80 degrees C-treated minor fimbriae. The anti-minor fimbria serum also reacts with the same-molecular-size fimbrial preparation from the wild-type strain. Immunogold electron microscopy showed that the anti-minor fimbria serum bound to the minor fimbria on the cell surface of the wild-type strain. This is the first report on the identification of the minor fimbria produced by P. gingivalis. These results suggest that the minor fimbriae appearing on the fimA mutant strain are produced together with numerous long major fimbriae on the wild-type strain. Moreover, the minor fimbriae are different in size and antigenicity from the earlier-reported FimA, a major 41-kDa fimbrial component of P. gingivalis.